Drawing skills lab - Ewasiuk, Sandee (Crabtree Publishing Company, 2019)
"This instructive art book inspires children to unleash their creativity as they learn how to use a variety of tools, media, and processes to create original drawings. Mini-bio sections highlight the work of well-known artists and encourage readers to consider the artist's use of the elements of art and principles of design. Skill-building projects support readers as they learn techniques including perspective, shading, shadowing, and more"--
Get into drawing -- Materials and colors -- Get started with doodling -- It's all about the contours -- Scribble art -- Shape + shape = form -- Grid head -- Stop action -- Hatch that -- Tonal shade -- The space between -- Overlapping fish -- That's one perspective -- Learning more.
Includes index.
Ages 9-12.
Grades 7 to 8.
Keywords: Drawing -- Technique -- Juvenile literature; Design -- Technique -- Juvenile literature; Artists -- Biography -- Juvenile literature; Drawing -- Technique; Art -- Technique; Artists -- Biography